An Analysis of Translation Quality and Difficulties Faced by the Twelfth Grade Students of SMA N 1 Koto Baru in Translating Explanation Texts from English to Bahasa Indonesia - Aan Pranata; Rusdi Noor Rosa (Universitas Negeri Padang, 2023)
This research investigates the students’ translating quality and difficulties in translating Explanation text from English into Bahasa Indonesia. This research is qualitative research. The sample of this research is 26 students in twelfth science one, selected by using technique of random sampling. To get the data, the researcher used two instrument, they are test to find out the translation quality and questionnaire to find out the difficulties. Based on the result, students’ translation quality in translating explanation text were mostly in good quality, with mean score 7,826. However the researcher found that the most difficulties in translating explanation text are linguistic factors, where the linguistic factor dominates students' difficulties compared to non-linguistic factors. although students can translate text explanations, students still need to fix their difficulties when translating explanation text, so that in the future they can improve their skills in translating